Ore genesis of the large Luobugaizi lead-zinc deposit in Xinjiang, NW China: constrains from lead isotope, in-situ trace elements and sulfur isotope of sulfides - Huang, Rui-Hong; Zhao, Hai-Xiang; Wang, Jia-Xin; Zhang, Chuan-Lin (Frontiers in Earth Science, 2026)
The recently discovered large Luobugaizi Pb-Zn deposit, located at the junction of the South Pamir and Karakoram Mountains, is a key component of the West Kunlun–Karakoram Pb-Zn Metallogenic Belt. Mineralization occurs mainly within the clastic rocks of the Silurian Wenquangou Formation, with ore minerals dominated by sphalerite and galena. This study focuses on the chemical composition of sphalerite and S-Pb isotopic characteristics of sulfides from the deposit to constrain its mineralization temperature, elemental substitution mechanisms, and metal sources. Sphalerite at Luobugaizi is characterized by relatively high concentration of Fe, Mn, Cd, Co and Sb, and relatively low concentration of Ge, Ag, In and As. Several elements, including Fe, Co, Cu, Ag, Ga, Ge, and In, substitute into the sphalerite lattice. Given the temperature-dependent nature of sphalerite trace element contents, it serves as a reliable geothermometer. The formation temperature of sphalerite was calculated using three distinct methods (Fe/Zn, GGIMF, and SPRFT software), with the average values ranging from 195 °C to 257 °C, indicating low-medium temperature hydrothermal conditions. The δ34SV-CDT values of sphalerite range from −1.2‰ to +3.3‰, suggesting a magmatic-hydrothermal sulfur source. Lead isotope compositions of sulfides (206Pb/204Pb = 18.41–18.44; 207Pb/204Pb = 15.70–15.71; 208Pb/204Pb = 38.70–38.76) are identical to those of local Cretaceous granitoids, which are considered a potential metal source. Crucially, published geochronological data indicate that the emplacement ages of these granitoids are consistent with the mineralization age of the Luobugaizi deposit. These granitoids were interpreted in previous studies as products of crust-mantle interaction during the northward subduction of the Tethyan oceanic slab. Therefore, we propose that the metals were likely sourced from a coeval magmatic system related to these granitoids and were deposited by magmatic-hydrothermal fluids in fractures of the clastic sequence. Integrated evidence classifies the Luobugaizi deposit as a magmatic-related, low-to medium-temperature hydrothermal system.